2014
DOI: 10.1021/jz500794d
|View full text |Cite
|
Sign up to set email alerts
|

How to Get Insight into Amyloid Structure and Formation from Infrared Spectroscopy

Abstract: There is an enormous amount of interest in the structures and formation mechanisms of amyloid fibers. In this Perspective, we review the most common structural motifs of amyloid fibers and discuss how infrared spectroscopy and isotope labeling can be used to identify their structures and aggregation kinetics. We present three specific strategies, site-specific labeling to obtain residue-by-residue structural information, isotope dilution of uniformly labeled proteins for identifying structural folds and protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
277
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 243 publications
(297 citation statements)
references
References 68 publications
20
277
0
Order By: Relevance
“…The comparison of the 1D-IR spectrum (in which the total oscillator strength is to a good approximation conserved) and the 2D-IR spectrum (in which the signal is nonlinearly dependent on the transition dipole of the IR modes4142) provides a measure of the excitonic delocalization of each structural component, making a combination of the techniques exceptionally useful to study amyloid systems, as has been shown by the work of the Zanni group43444546.…”
Section: D-ir On Amyloid Fibrilsmentioning
confidence: 99%
“…The comparison of the 1D-IR spectrum (in which the total oscillator strength is to a good approximation conserved) and the 2D-IR spectrum (in which the signal is nonlinearly dependent on the transition dipole of the IR modes4142) provides a measure of the excitonic delocalization of each structural component, making a combination of the techniques exceptionally useful to study amyloid systems, as has been shown by the work of the Zanni group43444546.…”
Section: D-ir On Amyloid Fibrilsmentioning
confidence: 99%
“…1A) and long-range order along the protein backbone. 24 The couplings delocalize the vibrations, so that multiple amides along and across the β-strands vibrate in unison. Delocalization, in turn, changes the absorption frequencies, absorptivity coefficients, and anharmonicities, creating diagonal peaks and off-diagonal cross peaks (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional IR spectroscopy has often been used to measure femto-to picosecond dynamics of liquids, proteins, catalysts, and many other bulk systems at high concentrations or surface areas (11)(12)(13). When 2D IR was first invented 15 y ago, it was considered an achievement to measure spectra at millimolar protein concentrations, because that is the typical concentration used for protein NMR spectroscopy.…”
Section: Methods and Applications Of 2d Ir With Monolayer Sensitivitymentioning
confidence: 99%